The American Academy of Pediatrics hypertension guidelines identify obese youth at high cardiovascular risk among individuals non-hypertensive by the European Society of Hypertension guidelines. (29th August 2020) - Di Bonito, Procolo; Licenziati, Maria Rosaria; Baroni, Marco G; Maffeis, Claudio; Morandi, Anita; Manco, Melania; Miraglia del Giudice, Emanuele; Di Sessa, Anna; Campana, Giuseppina; Moio, Nicola; Gilardini, Luisa; Chiesa, Claudio; et al.
Abstract: Background: Two different systems for the screening and diagnosis of hypertension (HTN) in children currently coexist, namely, the guidelines of the 2017 American Academy of Pediatrics (AAP) and the 2016 European Society for Hypertension (ESH). The two systems differ in the lowered cut-offs proposed by the AAP versus ESH. Objectives: We evaluated whether the reclassification of hypertension by the AAP guidelines in young people who were defined non-hypertensive by the ESH criteria would classify differently overweight/obese youth in relation to their cardiovascular risk profile. Methods: A sample of 2929 overweight/obese young people (6–16 years) defined non-hypertensive by ESH (ESH – ) was analysed. Echocardiographic data were available in 438 youth. Results: Using the AAP criteria, 327/2929 (11%) young people were categorized as hypertensive (ESH – /AAP + ). These youth were older, exhibited higher body mass index, Homeostatic Model Assessment of Insulin Resistance (HOMA-IR), triglycerides, total cholesterol to high-density lipoprotein cholesterol (TC/HDL-C) ratio, blood pressure, left ventricular mass index and lower HDL-C ( p <0.025–0.0001) compared with ESH – /AAP – . The ESH – /AAP + group showed a higher proportion of insulin resistance (i.e. HOMA-IR ≥3.9 in boys and 4.2 in girls) 35% vs . 25% ( p <0.0001), high TC/HDL-C ratio (≥3.8 mg/dl) 35% vs . 26% ( p = 0.001) and left ventricular hypertrophy (left ventricular mass index ≥45 g/h 2.16 ) 67% vs . 45% ( p = 0.008) as compared with ESH – /AAP – . Conclusions: The reclassification of hypertension by the AAP guidelines in young people overweight/obese defined non-hypertensive by the ESH criteria identified a significant number of individuals with high blood pressure and abnormal cardiovascular risk. Our data support the need of a revision of the ESH criteria.